Adsorptive Ability of Banana Stalks Biochar in Greywater Remediation for Reuse: A Case of University of Embu, Kenya - Ndung'u, Paul (University of Embu, 2020)
The global demand for fresh water resources has been increasing over the years due to population growth, urbanization, industrialization, climate change and the global warming effect. The available water resources have reduced over time leaving a water demand deficit. Recycling and reuse of greywater has been touted as one of the strategies to augment the existing water resources. This study characterized the greywater from students’ hostels and prepared biochar from banana stalks for use as an adsorbent in greywater remediation. The study found significant differences in greywater quality based on source, day and time of sampling. The biochar produced through pyrolysis at pyrolytic temperatures of 300 °C, 400 °C and 500 °C showed the presence of hydroxyl and carboxyl surface functional groups responsible for adsorption of target contaminants. The biochars achieved varying percentage reduction of the selected parameters with biochar prepared at temperature 500 °C recording a significantly higher (p≤ 0.05) percentage removal of Na + + and COD at 65.43%, 89.36% and 60.60% when compared to 58.30%, 56.96% and 49.51% for biochar 400 , K C, and 41.13%, 40.36% and 38.31% for biochar 300 °C, respectively. Biochar produced at temperature 300 °C exhibited a significantly higher (p≤ 0.05) reduction of BOD in the greywater of 71.28% as compared to biochars 400 °C and 500 °C which had 66.64% and 61.92% percentage reduction, respectively. Biochar 500 °C was found most suitable for Na ° an COD reduction while Biochar 300 °C most suited the BOD reduction. The results from this study showed that biochar produced from banana stalks can be used as an adsorbent for greywater remediation and the treated water was suitable for consideration in agricultural reuse under the test conditions.
Thesis